2016
DOI: 10.1371/journal.pone.0149511
|View full text |Cite
|
Sign up to set email alerts
|

Mapping National Plant Biodiversity Patterns in South Korea with the MARS Species Distribution Model

Abstract: Accurate information on the distribution of existing species is crucial to assess regional biodiversity. However, data inventories are insufficient in many areas. We examine the ability of Multivariate Adaptive Regression Splines (MARS) multi-response species distribution model to overcome species’ data limitations and portray plant species distribution patterns for 199 South Korean plant species. The study models species with two or more observations, examines their contribution to national patterns of specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 25 publications
(45 reference statements)
1
21
0
1
Order By: Relevance
“…The maximum sum of the sensitivity and specificity (MaxSSS) threshold is appropriate to convert the continuous probability map to a binary map when only presence data are available (Liu, Newell, & White, ; Liu, White, & Newell, ). This is a widely used threshold that has been used in similar studies (Bista et al, ; Choe, Thorne, & Seo, ; KC et al, ). In this study, we used the MaxSSS threshold to generate the final suitable habitat maps.…”
Section: Methodsmentioning
confidence: 99%
“…The maximum sum of the sensitivity and specificity (MaxSSS) threshold is appropriate to convert the continuous probability map to a binary map when only presence data are available (Liu, Newell, & White, ; Liu, White, & Newell, ). This is a widely used threshold that has been used in similar studies (Bista et al, ; Choe, Thorne, & Seo, ; KC et al, ). In this study, we used the MaxSSS threshold to generate the final suitable habitat maps.…”
Section: Methodsmentioning
confidence: 99%
“…However, for species richness in the rarity categories, we found that Gangwon province (northeastern South Korea) contains the highest species richness, especially for species with narrow geographic ranges. The primary mountain ranges of South Korea, including the highly biodiverse Baekdudaegan Mountains (Choe et al, ; Ministry of Environment, ), are mostly located in Gangwon province. Our study also found high species richness of rarity classes and of nationally listed endangered and endemic species in each rarity class in these mountains (Figure and Figure ), which indicates our simple approach can identify high biodiversity areas for rare species.…”
Section: Discussionmentioning
confidence: 99%
“…Uncertainties in SDM results arise from the quantity and quality of observation data, from predictor variables used, and from errors in the modeling (Elith & Leathwick, 2009). Model results are influenced significantly by the sample size (Hernandez, Graham, Master, & Albert, 2006), and in many cases, the number of records available to fit a reliable model is limited, particularly for many rare species and regions (Choe, Thorne, & Seo, 2016;Wisz et al, 2008). Furthermore, the testing of the model performance is not sufficient in many SDM studies to convince ecologists (Vaughan & Ormerod, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used the SDM results modeled using only climate parameters, but, in reality, the distributions of species are confined by interactions with other species [56]. We did not consider the capacity of species to reach the future climate suitable regions, and stacking species' ranges may tend to overestimate species richness [58,59]. Therefore, future species richness may be lower than projected, so uncertainties caused by using SDMs for predicting the impacts of climate change should be understood by policy makers.…”
Section: Model Assumptions and Limitationsmentioning
confidence: 99%